EFEKTIVITAS TERAPI MUROTTAL AL-QUR’AN TERHADAP SKOR HALUSINASI PASIEN HALUSINASI - Mimi Aisyah; Jumaini Jumaini; Safri Safri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Hallucinations are disorders or changes in perception where patients perceive something that actually doesn't happen. An appreciation experienced by a perception through the external senses of stimulus: false perception. Hallucinatory control can be done with one of the therapeutic modalities, namely psychiatric therapy. One of the psychological therapies that can be used is the media of the Qur'an, especially the verses of the Qur'an which are common to meruqyah, namely surah Al-Fatihah, Ayat Kursi, Al-Kafirun, Al-Ikhlas, Al-Falaq, and An-Nas . This study aims to determine the effectiveness of murottal Al-Qur'an therapy on hallucinatory scores. This study uses a pretest-posttest design with control groups. The sample of this study was 33 respondents who were divided into 17 respondents in the experimental group and 16 respondents in the control group were taken based on inclusion criteria using a purposive sampling technique. Each experimental group was given intervention for 6 consecutive days. The measuring instrument used is the Hallucination Rating Scale (HRC) that has been standardized. The analysis used was univariate analysis using the Dependent sample T test and bivariate analysis using the Independent sample T test. Statistical results were obtained p value (0,000) < (α = 0,05) so it can be concluded that there were significant differences between the experimental group and the control group after murottal Al-Qur'an therapy on hallucination scores. Therefore, the Murottal Al-Qur'an therapy intervention is effective in reducing hallucinatory scores. The suggestions from researchers for nurses to apply murottal Al-Qur'an therapy to all mental disorders, because it has been proven in this study murottal Al-Qur'an therapy provides meaningful results on hallucinatory patients hallucination scores. Keywords: hallucination score, murottal Al-Qur'an, psychiatric therapy